An Efficient N‐Heterocyclic Carbene‐Ruthenium Complex: Application Towards the Synthesis of Polyesters and Polyamides. Issue 6 (4th February 2015) - Malineni, Jagadeesh; Keul, Helmut; Möller, Martin
Abstract : The ruthenium benzimidazolylidene‐based N ‐heterocyclic carbene (NHC) complex4 catalyzes the direct dehydrogenative condensation of primary alcohols into esters and primary alcohols in the presence of amines to the corresponding amides in high yields. This efficient new catalytic system shows a high selectivity towards the conversion of diols to polyesters and of a mixture of diols and diamines to polyamides. The only side product formed in this reaction is molecular hydrogen. Remarkable is the conversion of hydroxytelechelic polytetrahydrofuran ( M ¯ n = 1000 g mol −1 )—a polydispers starting material—into a hydrolytically degradable polyether with ester linkages ( M ¯ n = 32 600 g mol −1 ) and, in the presence of aliphatic diamines, into a polyether with amide linkages in the back bone ( M ¯ n = 16 000 g mol −1 ). Abstract : In the presence of an electron‐rich phosphine ligand (PCy3 ), the NHC‐ruthenium complex4 shows high efficiency for the direct synthesis of polyesters from diols and of polyamides from diols and diamines by catalytic dehydrogenation polycondensation, with hydrogen being the only side product.